Negatives inductances or not naturals - Nuñez Zuñiga, Teresa Esther (2008)
This article studies how we can do negatives inductances which result of synthetizer voltage and current waves which emulate that behavior. The circuits with the negative inductances were simulated and analyzed far the power factor correction.